Propensity score matching analysis of the effect of four or more antenatal care visits on basic childhood immunization in Ethiopia - Misganaw Guadie Tiruneh; Kaleb Assegid Demissie; Wubshet D. Negash; Melak Jejaw; Getachew Teshale; Mikias Mered Tilahun; Tesfahun Zemene Tafere; Asebe Hagos (Scientific Reports)
Abstract Globally, immunization prevents 3.5 to 5 million deaths annually from common childhood diseases. Several observational studies evidenced that childhood immunization was linked to mothers’ Antenatal Care (ANC) visits. However, the effect of the number of ANC visits on childhood immunization in Ethiopia using propensity score matching has not been investigated. Therefore, this study aimed to assess the effect of four or more ANC visits on childhood immunization in Ethiopia using propensity score matching analysis. This secondary data analysis used the 2019 Ethiopian Mini Demographic and Health Survey, which included mothers whose most recent (index) birth occurred within the five years preceding the survey, with children aged 12–23 months. A propensity score matching (PSM) analysis was performed using a probit model with the psmatch2 command in STATA to estimate the average treatment effect on the treated (ATT), untreated (ATU), and the population (ATE). Common support assumptions were checked, and sensitivity analysis was done by Mantel-Haenszel bounds. A total of 972 mothers were included in this study. The overall basic immunization coverage was 39.72% (95% CI: 36.67, 42.82), and it was significantly higher among those mothers who received ANC 4 + visits (56.93%) when compared to mothers with < 4 ANC visits (27.09%). In the PSM analysis, the ATT values in the treated and control groups were 59% and 48%, respectively, indicating that the basic immunization coverage was increased by 11% (95% CI: 3.00, 17.00) because of the number of ANC visits. The ATU in the intervention and control groups were 27% and 45%, respectively, indicating that those mothers who had < 4 ANC visits, the chance of getting their children immunized would have increased by 18%, if they had made ANC 4 + visits. The final ATE estimate was 13% (95% CI: 5.00, 18.00) among the study participants. After matching, there was no significant difference in baseline characteristics between the treated and control groups (p-value > 0.05), which indicates the quality of matching was satisfactory. Enhancing mothers to have four or more ANC visits could effectively increase the uptake of basic childhood immunization in Ethiopia. Therefore, we recommend policy makers to enhance interventions targeting improving number of ANC visits to increase childhood immunization in Ethiopia.